Studi Empiris Faktor-Faktor Mempengaruhi Kualitas Audit pada Inspektorat Kota Padang - Frandika, Hezrina; Sari, Vita Fitria (Jurnal Eksplorasi Akuntansi, 2025)
The purpose of this study is to look at how the professionalism, job experience, and motivation of auditors affect the quality of their audits. Although prior research has shown inconsistent results, these characteristics are thought to be significant drivers of audit quality in the audit literature. Regression analysis and a quantitative method were used to gather data from a survey of auditors working at a public accounting firm in Medan City. The analysis's findings demonstrated that, although the auditor's work experience and motivation for the job did not significantly affect the audit's quality, their professionalism did. These findings emphasize the importance of focusing on developing a professional attitude in improving audit quality, which can be a foundation for audit practitioners in improving their practice. The practical implications of these findings include the expansion of auditor training and professional development in the audit industry, as well as the need for regulators to strengthen policies that support ethical standards and professionalism in audit practice. However, more investigation can uncover other variables that could impact audit quality and expand knowledge of the intricate interrelationships among these variables across a range of organisational and sector settings. Therefore, this study adds significantly to our knowledge of the variables influencing audit quality and offers guidance for future audit practice and research.